Derivation of CaO-SiO2-Al2O3system slag viscosity equation by GP - Ri S.-C.; Ra J.-H.; Ryom K.-C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Slag viscosity is essential in high-temperature metallurgical processes. However, a slag viscosity model is difficult to exactly interpret as it has a strong nonlinear relation with its composition and temperature. In this paper, genetic programming (GP) was employed to derive a CaO-SiO2-Al2O3 slag viscosity equation. The equation was automatically described as a simple algebraic equation with the basicity and content of Al2O3 and temperature. The average relative error between the values obtained by the equation and the experimental data used for its derivation was as low as 17.1%. Computer simulations were performed to evaluate the accuracy of the derived viscosity equation and were then compared with many experimental viscosities and calculated values of other researchers. Slag compositions and temperatures for simulation calculations were the experimental data which were not used for deriving a viscosity equation. The results showed that the viscosity equation was relatively exact. The viscosities of CaO-SiO2-Al2O3 system slag could be simply and expediently predicted within the wide range of compositions and temperatures by using the derived viscosity equation.